2015
DOI: 10.1002/adhm.201500099
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 3D Scaffolds with Precisely Controlled Substrate Modulus and Pore Size by Templated‐Fused Deposition Modeling to Direct Osteogenic Differentiation

Abstract: Scaffolds with tunable mechanical and topological properties fabricated by templated‐fused deposition modeling promote increased osteogenic differentiation of bone marrow stem cells with increasing substrate modulus and decreasing pore size. These findings guide the rational design of cell‐responsive scaffolds that recapitulate the bone microenvironment for repair of bone damaged by trauma or disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…This observation is consistent with reports that cells are in a state of isometric contraction and cannot sense changes in matrix rigidity above 0.1 MPa 19, 22 . However, in a recent study, we found that osteoblast differentiation and mineralization of osteoprogenitor cells cultured on 3D scaffolds increased with substrate rigidity over the range 20 – 300 MPa 17 . These findings are in agreement with a previous study reporting that expression of Runx2 and Alp increased with 2D substrate modulus when MC3T3-E1 pre-osteoblasts were cultured on PEG-diacrylate hydrogels (0.6 MPa) or tissue culture polystyrene (2000 MPa) 16, 45 .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This observation is consistent with reports that cells are in a state of isometric contraction and cannot sense changes in matrix rigidity above 0.1 MPa 19, 22 . However, in a recent study, we found that osteoblast differentiation and mineralization of osteoprogenitor cells cultured on 3D scaffolds increased with substrate rigidity over the range 20 – 300 MPa 17 . These findings are in agreement with a previous study reporting that expression of Runx2 and Alp increased with 2D substrate modulus when MC3T3-E1 pre-osteoblasts were cultured on PEG-diacrylate hydrogels (0.6 MPa) or tissue culture polystyrene (2000 MPa) 16, 45 .…”
Section: Discussionmentioning
confidence: 70%
“…We varied the molecular weight of the polyester triol component from 3000 to 300 g mol −1 to synthesize films with moduli ranging from 5 – 266 MPa (Fig. 1A) while maintaining a relatively constant contact angle of 60 – 65° 17 . Rat bone marrow-derived MSCs were plated on PUR films, which were pre-incubated in a solution of fibronectin (4 ug/mL) to facilitate cell attachment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The architecture in the tissue milieu of interest has proven to play a large role in cell differentiation, proliferation, metabolic activity, and motility. 31,57,72 Thus, creating the appropriate architecture in addition to the chemical and mechanical properties of the specific tissue is necessary if in vivo conditions are to be accurately simulated.…”
Section: D Tissue-engineered Constructs (Tecs) For Modeling Disease mentioning
confidence: 99%
“…1C). 31 While pore sizes > 100 μm can be printed using FDM, the small number of thermoplastic polymers that can be printed limits the range of substrate moduli that can be achieved. In the t-FDM approach, a template is printed by FDM which is subsequently filled with a two-component reactive poly(ester urethane) with substrate moduli ranging from 20 MPa (collagen fibrils) to 266 MPa (trabecular bone) (Fig.…”
Section: D Models Of Disease Progression and Drug Screeningmentioning
confidence: 99%